Dpp Signaling Activity Requires Pentagone to Scale with Tissue Size in the Growing Drosophila Wing Imaginal Disc - Hamaratoglu, Fisun; de Lachapelle, Aitana Morton; Pyrowolakis, George; Bergmann, Sven; Affolter, Markus (PLOS Biology, 2011)
The activity of the Dpp morphogen adapts to tissue size in the growing Drosophila wing imaginal disc, and Pentagone, an important secreted feedback regulator of the Dpp pathway, is required for this adaptation.